Profiles of teaching practices and reading skills at the first and third grade in Finland and Estonia. (May 2017) - Tang, Xin; Kikas, Eve; Pakarinen, Eija; Lerkkanen, Marja-Kristiina; Muotka, Joona; Nurmi, Jari-Erik
Abstract: The Early Childhood Classroom Observation Measure was used to observe 91 first-grade and 70 third-grade teachers in Estonia and Finland. Using a person-oriented approach, four profiles of teaching practices were identified in grade 1: the child-centred style, teacher-directed style, child-dominated style and a mixture of the child-centred and teacher-directed styles. An additional profile, the extreme-child-centred style, was found in grade 3. Children taught by child-centred teachers showed the highest reading skills, whereas children taught by child-dominated teachers showed the lowest skills. More Estonian than Finnish teachers applied the child-dominated style in grade 1 and the extreme-child-centred style in grade 3. Highlights: Using person-oriented approach to identify different profiles of teaching practices. Child-centred style was most beneficial while child-dominated style was least beneficial for reading skills. Mixture of child-centred and teacher-directed style was beneficial in grade 3. Extreme-child-centred style did not guarantee reading fluency in grade 3. Less beneficial styles showed more in Estonian teachers than in Finnish teachers.